In vitro combined treatment with cetuximab and trastuzumab inhibits growth of colon cancer cells. (8th August 2014) - Luca, T.; Barresi, V.; Privitera, G.; Musso, N.; Caruso, M.; Condorelli, D. F.; Castorina, S.
Abstract Objectives Overexpression or constitutive activation of epidermal growth factor receptors (EGFR) is involved in growth of human cancers. We investigated effects of EGFR and HER‐2 blockade in colon cancer cell lines using cetuximab and trastuzumab, with the aim of developing novel approaches to cancer therapy. Materials and methods We studied effects of treatment on cell growth, cell cycle distribution, induction of apoptosis, changes in EGFR and HER‐2 mRNA‐protein expression and EGFR and HER‐2 gene copy number in Caco‐2, HT‐29 and HCT‐116 cells. Results Treatment of cells resulted in no effect in one of the three cell lines and in inhibition of cell proliferation in a time‐ and dose‐dependent manner in the other two, with modulation of EGFR and HER‐2 mRNA and protein levels. Differences in sensitivity to cetuximab and trastuzumab were observed. Treatment induced specific changes in cell cycle distribution in both cell lines affected, while apoptosis was not increased. Fluorescence in situ hybridization analysis revealed abnormal copy number of two genes resulting from aneuploidy; this was not responsible for different sensitivity to combination between the two cell lines. Conclusions Targeting EGFR and HER‐2 simultaneously could have useful applications in colorectal cancer treatment. To improve pharmacological efficacy of cetuximab and trastuzumab combination, molecular mechanisms involved in their activity need to be elucidated.